Revisiting the Crustal Structure and Kinematics of the Central Andes at 33.5°S: Implications for the Mechanics of Andean Mountain Building. Issue 5 (15th May 2018) - Riesner, Magali; Lacassin, Robin; Simoes, Martine; Carrizo, Daniel; Armijo, Rolando
Abstract: The Andean belt is the only present‐day active case example of a subduction‐type orogeny. However, an existing controversy opposes classical views of Andean growth as an east verging retro wedge, against a recently proposed bivergent model involving a primary west vergent crustal‐scale thrust synthetic to the subduction. We examine these diverging views by quantitatively reevaluating the orogen structural geometry and kinematics at the latitude of 33.5°S. We first provide a 3‐D geological map and build an updated section of the east vergent Aconcagua fold‐and‐thrust belt (Aconcagua FTB), which appears as a critical structural unit in this controversy. We combine these data with geological constraints on nearby structures to derive a complete and larger‐scale section of the Principal Cordillera (PC) within the fore‐arc region. We restore our section and integrate published chronological constraints to build an evolutionary model showing the evolving shortening of this fore‐arc part of the Andes. The proposed kinematics implies uplift of the Frontal Cordillera basement since ~20–25 Ma, supported by westward thrusting over a crustal ramp that transfers shortening further west across the PC. The Aconcagua FTB is evidenced as a secondary east verging roof thrust atop the large‐scale basement antiform culmination of the Frontal Cordillera. We estimate a shortening of ~27–42 km across the PC, of which only ~30% is absorbed by the Aconcagua FTB. Finally, we combine these findings with published geological data on the structure of the eastern back‐arc Andean mountain front and build a crustal‐scale cross section of the entire Andes at 33.5°S. We estimate a total orogenic shortening of ~31–55 km, mainly absorbed by crustal west vergent structures synthetic to the subduction. Our results provide quantitative key geological inferences to revisit this subduction‐type orogeny and compare it to collisional alpine‐type orogenic belts. Key Points: Three‐dimensional structural map and revisited geological cross section of the Aconcagua fold‐and‐thrust belt at 33°S and 33.5°S Kinematics of crustal deformation and shortening of the Central Andes at 33.5°S since ~20–25 Ma Bivergent crustal‐scale model of the Andes at 33.5°S with a total orogenic shortening of ~31–55 km